A conceptual core competency model for halal executives in food manufacturing companies - Nik Mohd Rosli, N. R; Huda., F. H.; Ahmad Fadzillah, Nurrulhidayah; Hashim, Yumi Zuhanis Has-Yun; Ahmad, Anis Najiha (2022)
A competent halal executive is essential and an integral part of the Halal Management System in Halal-certified companies. Core competencies in general are linked with job productivity, job performance, and organisational performance. In Malaysia, initiatives are currently underway to produce competent and professional Halal executives. As for now, the competencies of halal executives are yet to be defined. Defining and identifying the core competencies is pivotal as the Malaysian Halal industry needs to appoint more competent halal executives to serve the halal-certified companies. Thus, this article aims to identify the set of competencies for halal executives via a literature review. This would allow for the further development of the Halal executive core competencies conceptual model. In addition, the background of Halal executives in the Malaysian Halal industry is also discussed to provide context for this review article. The conceptual model proposed is useful in discussing and developing the idea of core competencies, especially in the halal manufacturing industry context. A comprehensive core competencies model is useful for preparing future halal executives, evaluating halal executives' practises in the workplace, and for their lifelong professional development. Other countries could use the same core competencies framework to inform the development of the human resource related to Halal.